Liver Transplantation for Hepatocellular Carcinoma in Patients with Inherited Metabolic Liver Diseases: A Single-Center Analysis - Garzali, İbrahim Umar and Hargura, Abdirahman Sakulen and İnce, Volkan and Varol, Fatma İlknur and Carr, Brian I. and Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2023)
Background/Aims: Liver transplantation is an acceptable treatment for some selected hepatocellular carcinoma. We report our experience of 6 patients with liver transplantation for hepatocellular carcinoma with background inherited metabolic disease. Materials and Methods: This is a single-center retrospective, descriptive study. Consecutive patients who underwent liver transplantation for hepatocellular carcinoma with background inherited metabolic disease were included in the study. The record of the patients was accessed, and the following data were extracted: sociodemographic variables, type of metabolic disease, date of liver transplantation, tumor characteristics, laboratory parameters, Model for End-Stage Liver Disease score, immediate- and long-term outcome after transplantation, disease-free survival, and overall survival. Data were analyzed using Statistical Package for the Social Sciences version 25.0. Results: Six patients received liver transplantation for hepatocellular carcinoma with background inherited metabolic liver disease. The median age was 4.5 years. The median Model for End-Stage Liver Disease score was 29.30. The median maximum tumor diameter was 2.15 cm. Three patients had multiple tumor nodules. Half of the patients had microvascular invasion. Four of the patients had a moderately differentiated tumor. Progressive familial intrahepatic cholestasis type II is the commonest inherited metabolic disease seen in 3 patients. Median follow-up is 46.1 months. Half of the patients are currently more than 5 years post liver transplantation with no features of recurrence. The estimated survival rates at 1, 3, and 5 years are 100%, 83.3%, and 83.3%, respectively. Conclusion: Liver transplant for these categories of patients is associated with good disease-free and overall survival, even in the presence of some seemingly poor prognostic features. Cite this article as: Garzali İU, Hargura AS, İnce V, Varol Fİ, Carr BI, Yılmaz S. Liver transplantation for hepatocellular carcinoma in patients with inherited metabolic liver diseases: A single-center analysis. Turk J Gastroenterol. 2023;34(12):1235-1239.